2005
DOI: 10.1089/acm.2005.11.631
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Blinded, Randomized Pilot Study Evaluating the Aroma of Lavandula augustifolia as a Treatment for Mild Insomnia

Abstract: Background: Insomnia is the most common of all sleep complaints and is under-researched. The current treatments of choice are conventional hypnotics agents, but these have potential for serious adverse reactions. Uncontrolled and anecdotal evidence suggests that lavender oil is an effective treatment for insomnia, but this has not been formally investigated.Objectives: The aims of this study were to evaluate the proposed trial methodology and the efficacy of Lavandula augustifolia (lavender) on insomnia.Interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
57
3
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 18 publications
1
57
3
4
Order By: Relevance
“…12 Moreover, lavender oil has been reported to improve sleep disorders. 13,14 It has also been reported that the essential oil of lemon affects the anti-oxidant action of vitamin E and improves the state of blood vessels near the skin. 15 Although there are few reports on aromatherapy in senile dementia, it has been suggested that aromatherapy may bring about some feeling of relief and the ability to act on outside influences such that the obstacle to action in senile dementia can be coped with.…”
Section: Introductionmentioning
confidence: 99%
“…12 Moreover, lavender oil has been reported to improve sleep disorders. 13,14 It has also been reported that the essential oil of lemon affects the anti-oxidant action of vitamin E and improves the state of blood vessels near the skin. 15 Although there are few reports on aromatherapy in senile dementia, it has been suggested that aromatherapy may bring about some feeling of relief and the ability to act on outside influences such that the obstacle to action in senile dementia can be coped with.…”
Section: Introductionmentioning
confidence: 99%
“…9 Lavender aromatherapy can also reduce mild insomnia in patients in their home setting. 10 We chose lavender rather than another essential oil because of the studies that support using lavender to promote rest and relaxation in different settings. Little scientific research has been done to establish effects of lavender aromatherapy on sleep in an acute care hospital setting.…”
mentioning
confidence: 99%
“…11 Linalyl acetate produces narcotic effects. 11 Such effects are consistent with the analgesic, 12 soporific, [13][14][15] and particularly anxiolytic 16,17 properties of lavender linked to relaxation and stress reduction. 2,18 However, human pharmacokinetic data for lavender essential oil metabolites are scarce, and little information is available regarding biological pathways associated with stress-reducing lavender effects.…”
Section: Introductionmentioning
confidence: 62%